Pengembangan Santri Melalui Tarbiyatul Mubaligh wal-Mubalighah di Pondok Pesantren Miftahul Khair Tebuireng VII Buyat - Ampel, Zikrullah (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
This study aims to describe the implementation, supporting and inhibiting factors, and positive impacts of Tarbiyatul Mubaligh wal-Mubalighah activities on the personal development of students at the Miftahul Khair Tebuireng VII Buyat Islamic Boarding School. This activity is one of the boarding school's flagship programs, which aims to train students' public speaking skills, build their confidence, and shape their character as prospective preachers. This study employs a descriptive qualitative method, utilizing data collection techniques that include observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion. The study was conducted over a period of two months, from November to December 2024. The results of the study show that this activity is carried out routinely every Saturday night, utilizing a group system that is rotated weekly. The series of events includes an MC, recitation of the Holy Quran, shalawat, poetry, hadith memorization, short lectures, and evaluation sessions. Supporting factors for this activity include the availability of facilities, intensive coaching, the existence of a student organization, and peer support. Meanwhile, the inhibiting factors include lack of confidence, minimal material preparation, santri absenteeism, and technical obstacles such as power outages. The positive impacts of this activity include improved communication skills, increased confidence, and enhanced teamwork skills among santri.